O conhecimento de neurociência cognitiva e a valorização por professores de cursos de licenciatura da área de ciências da natureza - Santos, Martha Rheingantz dos (2018)
This paper presents the results of the research conducted on the study of cognitive neuroscience in teacher training in the area of Natural Sciences. The central problem of research is expressed in the question: How do teachers of undergraduate courses in the area of Natural Sciences (Biology, Physics, Chemistry) of the Metropolitan Region of Porto Alegre value the knowledge in the area of Cognitive Neuroscience in teacher training? To propose answers to that question, some teachers of specific disciplines of degree courses in Biology, Physics and Chemistry of four universities in the metropolitan region of Porto Alegre were invited to participate in the research. The research had a qualitative approach and the type of research was the case study, in which the data were collected through questionnaires, semi-structured interviews, daily research and information record sheet obtained from the curricular structure of the courses and contents of disciplines. From the Discursive Textual Analysis - ATD, chosen method for the analysis of the results, emerged four categories of analysis. The research results indicate that knowledge about cognitive neuroscience is not well appreciated in teacher training, so that although the participants consider that that knowledge for teachers are important and exercising influence on the students' learning process, they are not explicitly inserted in their classes in undergraduate courses. However, there is evidence that there is some more implicit neuroscience study as the approach to questions about memory, attention, emotion and motivation, which are concepts related to the nervous system and cognition. Also, the lack of training and knowledge about brain functioning and neuroscience was evidenced by the majority of teachers interviewed.